Oral lichen planus and other confounding factors in narrow band imaging (NBI) during routine inspection of oral cavity for early detection of oral squamous cell carcinoma: a retrospective pilot study - Guida, Agostino (BMC Oral Health, 2019)
BACKGROUND: Narrow Band Imaging is a noninvasive optical diagnostic tool. It allows the visualization of sub-mucosal vasculature; four patterns of shapes of submucosal capillaries can be recognized, increasingly associated with neoplastic transformation. With such characteristics, it has showed high effectiveness for detection of Oral Squamous Cell Carcinoma. Still, scientific literature highlights several bias/confounding factors, such as Oral Lichen Planus. We performed a retrospective observational study on patients routinely examined with Narrow Band Imaging, investigating for bias, confounding factors and conditions that may limit its applicability. METHODS: Age, sex, smoking, use of dentures, history of head & neck radiotherapy, history of Oral Squamous Cell Carcinoma, site of the lesion and thickness of the epithelium of origin were statistically evaluated as possible bias/confounding factors. Pearson’s Chi-squared test, multivariate logistic regression, Positive Predictive Value, Negative Predictive Value, Sensitivity, Specificity, Positive Likelihood Ratio, Negative Likelihood Ratio and accuracy were calculated, normalizing the cohort with/without patients affected by Oral Lichen Planus, to acknowledge its role as bias/confounding factor. RESULTS: Five hundred fifty-six inspections were performed on 106 oral cavity lesions from 98 patients. Age, sex, smoking, use of dentures and anamnesis of Oral Squamous Cell Carcinoma were not found to influence Narrow Band Imaging. History of head & neck radiotherapy was not assessed due to insufficient sample. Epithelium thickness does not seem to interfere with feasibility. Presence of Oral Lichen Planus patients in the cohort led to false positives but not to false negatives. Among capillary patterns, number IV was the most significantly associated to Oral Squamous Cell Carcinoma (p < 0.001), not impaired by the presence of Oral Lichen Planus patients in the cohort (accuracy: 94.3, 95% confidence interval: 88.1–97.9%; odds ratio: 261.7, 95% confidence interval: 37.7–1815.5). CONCLUSION: Narrow Band Imaging showed high reliability in detection of Oral Squamous Cell Carcinoma in a cohort of patients with oral cavity lesions not normalized for bias/confounding factors. Still, Oral Lichen Planus may lead to false positives. Narrow Band Imaging could help in the follow-up of patients with multiple lesions through detection of capillary pattern IV, which seems to be the most significantly associated to neoplastic epithelium.